DAMPAK BULLYING DALAM PSIKOSOSIAL SISWA SMP NEGERI 3 MANDREHE TAHUN PELAJARAN 2023/2024 DAN IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING - Depiari Gulo (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
The problem of this research is the acts of bullying committed by the students of SMP Negeri 3 Mandrehe so the acts itself had an impact on the students’ psychosocial outcomes as victims of bullying. The purposes of this research are; (1) to know the kinds of bullying are done by the students of SMP Negeri 3 Mandrehe, and (2) to know the impacts of bullying on students’ psychosocial at grade of SMP Negeri 3 Mandehe. The kind of this research is qualitative research and and researcher used the descriptive approach. Then, the data in this research are the kinds of bullying and the impacts of bullying on students’ psychososial at grade of SMP Negeri 3 Mandrehe. The data itself obtained on the results of observation that conducted, on the results of interviews that done by researcher to the informants and obtained in SMP Negeri 3 Mandrehe’s documentations. The techniques of data collection in this research are observation, interview and documentation techniques. Furthermore, the data analysis technique is used in this research are data reduction, data display and drawing conclussion. The results of this research show that the kinds of bullying are done by the grade of SMP Negeri 3 Mandrehe are verbal bullying in the forms rants, ridicules and insults. Then, as thye impacts of bullying itself are the students as the victims of bullying felt feir, embarrassed and inferior so those students are not confident involving themselves in activities inside and outside of the classroom. Therefore, bullying can be an negative a negative impacts on students psychosocial as the victims of bullying. Then, as suggestions are proposed by the researcher namely; the results of this research should be used as consideration for improving the morals and ethics of students at school and in the community, and should be used as reference material for future researchers who will conduct the research in the relevant fields.